Biology and Management of Common Chickweed (Stellaria media) in Ornamental Crop Production - Yuvraj Christopher Khamare; Chris Marble; Nathan Boyd; Shawn Steed (EDIS)
Chickweed is a common cool-season annual weed in Florida landscapes, container nurseries, home gardens, and other agricultural production systems. This new 5-page article is written for green industry professionals and others to aid in the identification and management of chickweed in and around ornamental plants. Written by Yuvraj Khamare, Chris Marble, Nathan Boyd, and Shawn Steed and published by the UF/IFAS Environmental Horticulture Department. https://edis.ifas.ufl.edu/ep577